Eksplorasi dan Karakterisasi berbagai Kristal Ibuprofen - Yanuar, Arry; Nursanti, Nursanti; Anwar, Effionora (UI Scholars Hub, 2010)
Ibuprofen is an analgesic anti-inflammatory nonsteroidal (AINS). Generally, ibuprofen have a bad flowability because a high cohesivity. Another problem in manufacturing is the high tendency for sticking to the punches. Besides these disadvantageous properties, ibuprofen indicates bad dissolution behavior because of its hydrophobic structure. To improve the properties of ibuprofen can be used crystallization method with using variation of solvents. In this experiment observed crystallization method by cooling, evaporation, and water presence, which used methanol, ethanol, and acetone solvents. Of all the crystallization results are produced white prism-shaped crystalline. The selected method is cooling method, which is characterized using Scanning Electron Microscopy (SEM), powder X-ray diffraction, and Differential Scanning Calorimetry (DSC). These three characterizations indicate transformation of crystal form which compared with ibuprofen’s standard. The selected method also produces non cohesive powder which have the size particle is 710-1180µm, compressibility index: IBMD 14.2%, IBED 16.6%, IBAD 17.1%; angles of repose: IBMD 28.1º, IBED 29.7º, IBAD 30.1º, and have higher solubility than the common crystal’s solubility. The result indicates that crystallization method is able to improve flowrate, compressibility index, and dissolution rate properties of ibuprofen’s standard.